Customer brand co-creation behavior: conceptualization and empirical validation. Issue 3 (8th May 2018) - France, Cassandra; Grace, Debra; Merrilees, Bill; Miller, Dale
Abstract : Purpose: The purpose of this paper is to expand on existing co-creation knowledge in order to accurately conceptualize, operationalize and contextualize the customer brand co-creation behavior concept from a customer perspective. Design/methodology/approach: A quantitative approach is adopted in this study, using structural equation modeling to verify the co-creation of brand value for those customers who co-create. Findings: A new four-dimensional co-creation behavior concept is supported, highlighting the role of development, feedback, advocacy and helping, in the co-creation of brand value. Furthermore, a range of customer-level and brand-level antecedents are empirically verified. Research limitations/implications: The research takes a customer-centric view of co-creation and in doing so provides new insight into the effect on the co-creator. Additionally, the research offers an improved level of specificity in the co-creation domain by conceptualizing, operationalizing and contextualizing customer co-creation in a comprehensive research study. Practical implications: The findings offer new insight to brand managers, identifying avenues for increasing customer participation in co-creation programs and critically highlighting that co-creation behavior has positive effects on the co-creator's perception of brand value. Originality/value: The customer-centric approach offers an original perspective from which to explore co-creation, demonstrating the positive potential of co-creation in brand management strategies.